Sistem Alarm Pendeteksi Posisi Ternak Berbasis GPS dan SMS - Asmawaty Azis; Muh Sakir; Nurhalisa Nurhalisa (Program Studi Teknik Elektro Universitas Khairun, 2021)
Breeders pen or place cattle in the field or outdoors without safety equipment. With conditions like this, it is undeniable that if there is a cattle theft and it will cause great losses to the cattle owners, a solution to overcome this problem is to create a GPS and SMS based cattle position detection alarm system. Cattle detection system (cow collar) uses arduino mega, 800L sim module and GPS. By testing the alarm system using four conditions, namely cattle leaving a safe position in the north, south, east and west, the system manages to provide information (alarm sounds) on these four conditions withÂ . Meanwhile, the Livestock Detection System (SMS) was tested in four situations, namely when the cattle left a safe place at a distance of 10 meters, 30 meters, 50 meters, and 100 meters. Out of the five tests, the cattle detection system successfully sent information (sms) to the cattle owner's smartphone containing a Google map link for the position of the cattle at that distance.